Pengembangan Sistem Informasi Penjualan Sayuran berbasis Web dengan menggunakan Metode Waterfall Studi Kasus : (Agro Techno Park Universitas Brawijaya) - Riski Ida Agustiyan; Imam Cholissodin; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Agro Techno Park is a place for the development of agricultural products that are managed for agricultural entrepreneurship and a place for agricultural technology services. the purpose of the Agro Techno Park is as a center for the application of technology in agriculture, fisheries, and animal husbandry. One example of an Agro Techno Park located in East Java is owned by Brawijaya University which is located in Cangar and Jatikerto. In the marketing of Agro Techno Park products, UB still uses the manual method, namely by marketing products through the social network WhatsApp. By using this method, Agro Techo Park UB faces certain difficulties when receiving orders from customers. Because customers sometimes order products at the time of delivery, Agro Techno Park UB will come back again to take orders that have been added. In this case, of course, it takes a lot of time to make buying and selling transactions. People don't even know that Agro Tecno Park UB's vegetable products can be sold with quality vegetables. To solve this problem, the authors developed a Vegetable Sales Information System in Agro Techno Park UB. This system was developed to facilitate buying and selling transactions at Agro Techno Park UB and to expand the marketing segment of the vegetable products being sold. System development is carried out on a-based website and using the model waterfall using theprogramming PHP language on the Laravel framework. The system will be tested using the method white box, black box, integration testing, validation testing, and compatibility testing.